The STAD Learning Model Supported by Scientific Student Worksheets on Learning Outcomes and Collaboration Skills of Elementary School Students - Setiyaningsih, Ita; Sujarwo (Universitas Pendidikan Ganesha, 2023)
This research is motivated by the problem of the need for collaboration skills of students in working together in groups. In addition, many students still need to reach the minimum completeness criteria set by the school. This study aims to analyze and describe the effect of the STAD learning model, assisted by scientific worksheets, on elementary school students' learning outcomes and collaboration skills. The method used in this study is quasi-experimental. Learning outcomes were collected using multiple-choice tests, essays, and observation sheets to determine students' collaboration skills. The three hypotheses were tested using a Multivariate Analysis of Variance (Manova). The results showed significant differences in learning outcomes and collaboration skills between students who were taught with the STAD model assisted by scientific worksheets and students who studied without using the STAD model assisted by scientific worksheets. So it can be concluded that the STAD learning model, assisted by scientific worksheets, influences elementary school students' learning outcomes and collaboration skills. This research is expected to provide a contribution and reference for educators in applying learning models to improve student learning outcomes and collaboration skills.